A 27‐year review of mergers and acquisitions research in 27 leading management journals. (4th March 2020) - Gomes, Emanuel; Alam, Sunbir; Tarba, Shlomo Y.; Vendrell‐Herrero, Ferran
Abstract: This study contributes to the existing body of knowledge on mergers and acquisitions (M&As) by providing a systematic review of over 500 academic articles across 27 management journals over a 27‐year time frame. There appears to be a mixture of empirical and conceptual articles, with a larger proportion being empirical but an increasing number leaning towards a conceptual nature. Our findings show that most studies follow a quantitative approach and use large samples, mostly originating from existing databases. There is an emergence of thematic areas related to the strategic factors influencing M&As, but with the human dimension, gaining increasing attention over time.